Pelatihan Digital Marketing Dalam Meningkatkan Kompetensi Siswa untuk Berwirausaha Pada Sekolah-Sekolah di Kawasan Pantura (Lamongan-Gresik): Pelatihan Digital Marketing Dalam Meningkatkan Kompetensi Siswa untuk Berwirausaha Pada Sekolah-Sekolah di Kawasan Pantura (Lamongan-Gresik) - Aminin, Aminin (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Generation Z or students' interaction with the internet world is very active; since they were little, they have lived and been used to playing with gadgets. On average, students can access 7-10 hours/day. Activities can have positive value if the interaction is directed at positive activities. On the other hand, if it is not directed, the tendency is negative. Glagah District is rich in aquaculture products, capture fisheries, and even processing of fishery products. However, this potential has yet to be optimized as a business opportunity. Few people still sell fishery products online despite the significant business opportunities and broad market access. Its existence is essential to run; the business will remain in place without it—students with all their potential need to be directed to take advantage of these business opportunities. Through internal community empowerment activities at the Muhammadiyah University of Gresik, students will be given meaningful stimulus and education to be empowered when they graduate. This activity is carried out using lecture and practice methods. The result is that students grow in their entrepreneurial spirit, understand the region's potential, understand the characteristics of online buying and selling, and can brand various fishery products online.